PENGARUH INTELLECTUAL CAPITAL DAN ESG TERHADAP MANAJEMEN LABA YANG DIMODERASI OLEH PROFITABILITAS - Novita Andriani; Regina Jansen Arsjah (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to examine and analyze the effect of intellectual capital dan environmental, social, and governance on earnings management with profitability as a moderating variable. This research is quantitative research using secondary data. The population in this study are manufacturing and banking companies listed on the Indonesia Stock Exchange (IDX) in 2018 – 2020 period. The sample of this study amounted to 93 companies obtained by purposive sampling method. The data analysis method used is panel data regression analysis. Statistic tool used is e-views. The results of this study are intellectual capital and ESG has a negative effect on earnings management, profitability can strengthen the negative effect of intellectual capital and ESG on earnings management.